Combined GPS + BDS for short to long baseline RTK positioning - Odolinski, R.; Teunissen, Peter; Odijk, Dennis (Institute of Physics Publishing, 2015)
The BeiDou Navigation Satellite System (BDS) has become fully operational in the Asia-Pacific region and it is of importance to evaluate what BDS brings when combined with the Global Positioning System (GPS). In this contribution we will look at the short, medium and long single-baseline real-time kinematic (RTK) positioning performance. Short baseline refers to when the distance between the two receivers is at most a few kilometers so that the relative slant ionospheric and tropospheric delays can be assumed absent, whereas with medium baseline we refer to when the uncertainty of these ionospheric delays can reliably be modeled as a function of the baseline length. With long baseline we refer to the necessity to parameterize the ionospheric delays and (wet) Zenith Tropospheric Delay (ZTD) as completely unknown. The GNSS real data are collected in Perth, Australia. It will be shown that combining the two systems allows for the use of higher than customary elevation cut-off angles. This can be of particular benefit in environments with restricted satellite visibility such as in open pit mines or urban canyons.